Wearable and Portable Devices in Sport Biomechanics and Training Science - Diego Jaén-Carrillo; Alejandro Pérez-Castilla; Felipe García-Pinillos (Sensors, 2024)
Sport biomechanics and training have traditionally been tested under laboratory conditions, requiring specific settings and expensive equipment [...]